The effect of the problem-oriented project-based learning (POPBL) model on the environmental attitudes of students : POPBL - Ucik Agusti Wulanningsih; I. Ibrohim; Sofia Ery Rahayu (University of Muhammadiyah Malang, 2025)
There are several learning models that can improve students' environmental attitudes. This study aims to analyze the effect of problem-oriented project-based learning (POPBL) model on improving students' environmental attitudes. This research is a quasi-experiment using a pre-test and post-test control group design. The population of this study consisted of class X-10 as the experimental group, X-7 as the positive control group, X-8 as the negative control group. The results showed that POPBL model had a significant effect on improving the environmental attitudes of students of SMA Negeri 6 Malang. Covariance analysis showed a p-value of 0.000. < α (0.05). These results indicating that the application of the POPBL model in the experimental group resulted in a significant improvement compared to the control groups. Therefore, it can be concluded that the POPBL model is effective in enhancing students environmental attitudes.